Efektivitas Sistem E-learning Quipper School Pada Mata Pelajaran Bahasa Arab Kelas X MA Ihyaul Ulum Gresik - Adam Ahmad Syahrul Alim; Abdulloh Hamid (IAIN Sorong, 2020)
This is aim to find out the effect of the E-learning system using quipper school on readingcomprehension of the Arabic text. The problems of this study are: 1) Is there any effect of E-learn system using quipper school on reading comprehension of the Arabic text. 2) how students’ respoafter given reading comprehension material by E-learning system using Quipper School. achieve the research objectives, the writer used quantitative research methods with experimental design. The research subjects of this study were students of the tenth grade of Mipa 1 a2 in MA Ihyaul Ulum Gresik. The population is 60 students, each class is 30 students. The instruments used were tests and questionnaires. Data from statistical analysis tests using at-testing the significance of the difference in averages of the pre-test and post-test. The questionnaire was analyzed using a Likert scale and percentage formula. Based on these results, it shows that the t-test obtained 4.40. This value is higher than the t-table value, with a significance value of 0.052.00 for df 58. While the results of student responses are 80.1%. So, it can be concluded that the learning system using quipper schools on reading comprehension of Arabic text in MA Ihyaul UlGresik was successful. The results of this study were expected to use the E-learning system us quipper school to help students and teachers more easily during reading comprehension of the Aratext learning process.